Kajian Problematika Pendidikan Tinggi Islam - Alam, Abdal Malik Fajar; Tharaba, M. Fahim (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
The problems of Indonesian education in Islamic higher education include an irrelevant curriculum, limited infrastructure and resources, inequality of access and quality of education, the quality of teaching and research that needs to be improved, and low relevance to the needs of society. Solutions to the problems of Indonesian education in Islamic higher education include updating the relevant curriculum, improving infrastructure and resources, equalizing access and equity of education, improving the quality of teaching and research, and collaboration with industry and society. These steps require cooperation between the government, educational institutions, industry and society together. By implementing these solutions, it is hoped that Islamic higher education institutions in Indonesia can make a greater contribution to the development of society and the Islamic world.